2002
DOI: 10.1074/jbc.m109913200
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 and Cdc42 but Not RhoA or Rho Kinase Activities Are Required for Neurite Outgrowth Induced by the Netrin-1 Receptor DCC (Deleted in Colorectal Cancer) in N1E-115 Neuroblastoma Cells

Abstract: Netrins are chemotropic guidance cues that attract or repel growing axons during development. DCC (deleted in colorectal cancer), a transmembrane protein that is a receptor for netrin-1, is implicated in mediating both responses. However, the mechanism by which this is achieved remains unclear. Here we report that Rho GTPases are required for embryonic spinal commissural axon outgrowth induced by netrin-1. Using N1E-115 neuroblastoma cells, we found that both Rac1 and Cdc42 activities are required for DCC-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 49 publications
8
179
0
Order By: Relevance
“…It has been demonstrated that stimulant drugs enhance the ratio of AMPA/NMDA receptor-mediated glutamate neurotransmission in the VTA (Borgland et al, 2004;Boudreau and Wolf, 2005;Faleiro et al, 2004;Saal et al, 2003;Sarti et al, 2007;Ungless et al, 2001), an effect that depends on NMDA receptor neurotransmission at the time of drug treatment (Ungless et al, 2001). It has recently been shown that activity of the Rac1 Rho GTPase, a downstream netrin-1 effector (Li et al, 2002), enhances excitatory synaptic transmission by promoting AMPA receptor clustering (Wiens et al, 2005). Thus, the upregulation of DCC and UNC-5 receptors in the VTA may be involved in AMPH-induced plasticity of VTA DA circuitry by enhancing the availability of AMPA receptors at the synapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that stimulant drugs enhance the ratio of AMPA/NMDA receptor-mediated glutamate neurotransmission in the VTA (Borgland et al, 2004;Boudreau and Wolf, 2005;Faleiro et al, 2004;Saal et al, 2003;Sarti et al, 2007;Ungless et al, 2001), an effect that depends on NMDA receptor neurotransmission at the time of drug treatment (Ungless et al, 2001). It has recently been shown that activity of the Rac1 Rho GTPase, a downstream netrin-1 effector (Li et al, 2002), enhances excitatory synaptic transmission by promoting AMPA receptor clustering (Wiens et al, 2005). Thus, the upregulation of DCC and UNC-5 receptors in the VTA may be involved in AMPH-induced plasticity of VTA DA circuitry by enhancing the availability of AMPA receptors at the synapse.…”
Section: Discussionmentioning
confidence: 99%
“…shown that activity of the Rac1 Rho GTPase, a downstream netrin-1 effector (Li et al, 2002), enhances excitatory synaptic transmission by promoting AMPA receptor clustering (Wiens et al, 2005). Thus, the upregulation of DCC and UNC-5 receptors in the VTA may be involved in AMPH-induced plasticity of VTA DA circuitry by enhancing the availability of AMPA receptors at the synapse.…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A screen for genes controlling motor axon guidance led to the isolation of max-1, which genetically interacts with unc-5 and unc-6 but not with unc-40 in C. elegans 30 . In vertebrates, netrin signaling may involve phospholipase C (PLC) 31 , phosphoinositol-3-kinase (PI3K) 31 , MAP kinases 31-33 and the small GTPases Cdc42 and Rac 34,35 . FAK is a cytoplasmic protein tyrosine kinase that was discovered a decade ago [36][37][38][39][40] . FAK is involved in multiple cellular processes including adhesion, spreading, migration, survival, cell cycle progression and proliferation 41 .…”
mentioning
confidence: 99%
“…Netrin-1 binding to DCC activates Cdc42 and Rac1 in spinal commissural neurons 54,55 and dominant-negative Rac1 and Cdc42 inhibit DCC-mediated neurite outgrowth in neuroblastoma cells, whereas inhibition of RhoA or its effector Rho kinase increases axon extension in response to netrin-1. 56 Predominance of RhoA activation resulting from the expression of myelin inhibitory proteins and their receptors in the adult CNS 57-59 may overwhelm effects of myrDCCDP1 expression. Thus, although overexpression of myrDCCDP1 from our dual promoter lentiviral vector in rubrospinal and corticospinal axons in the adult spinal cord was not sufficient to promote axon regeneration, these experiments did show the feasibility of our approach in quantifying axonal growth responses to therapeutic gene candidate expression.…”
Section: Lentiviral Vector For Axon Regeneration Studiesmentioning
confidence: 99%